ARTIFICIAL INTELLIGENCE AND INDUSTRY TRANSFORMATION, EFFICIENCY AND INNOVATION (CIPEEX, 2025)
Artificial Intelligence (AI) is revolutionizing the industrial sector, promoting significant changes in the way companies operate, produce, and deliver their products. The adoption of AI technologies such as machine learning, computer vision, and advanced automation systems is enabling industries to optimize their processes, reduce operating costs, and improve the quality of the products and services they offer. This study aims to analyze the impacts of Artificial Intelligence on industry, highlighting the main areas of application, benefits, and challenges faced by companies in adopting these technologies. AI is being widely used to automate repetitive tasks, improve quality control, and increase the efficiency of production lines. AI systems can predict machine failures by analyzing data in real time, which reduces downtime and maintenance costs. In addition, the customization of mass production, driven by AI algorithms, allows companies to better meet customer needs by offering tailor-made products with greater agility. Another significant impact of AI on the industry is the capacity for predictive analysis, which uses large volumes of data to forecast market trends, adjust production levels, and optimize supply chains. This data-driven approach gives companies a competitive edge, enabling faster and more informed decisions. AI tools are also being applied to improve safety in the workplace, identifying risks in real time and suggesting preventative measures. Although the benefits are vast, the implementation of AI in industry faces challenges. The need for adequate technological infrastructure, high initial investment, and resistance to cultural change within organizations are some of the main obstacles. Cybersecurity is also a growing concern, as AI systems connected to the internet increase companies' vulnerability to cyberattacks. Additionally, there is a debate around the replacement of traditional jobs by automation, which raises concerns about the future of work. The integration of AI into industry is also opening up new opportunities for innovation. Collaborative robots, known as cobots, are working side by side with humans on tasks that require precision, strength, and repetitiveness, increasing productivity and safety. The application of AI in advanced robotics is allowing factories to be more flexible and adaptable to changes in demand. In addition, AI is being used to develop intelligent materials and additive manufacturing processes, such as 3D printing, which are redefining the boundaries of industrial design. In conclusion, Artificial Intelligence is a driver of transformation for industry, providing efficiency, innovation, and new ways of interacting with the market. For companies to maximize the benefits of this technology, it is essential to invest in training professionals, develop clear implementation strategies, and adopt robust cybersecurity practices. AI will continue to shape the future of industry, offering unlimited possibilities for creating value and continuously improving production processes.
Keywords: artificial intelligence; industry; automation; efficiency; innovation